(untitled) (Albayan Scientific Journal, 2023)
Sheep breeding is one of the most important activities that the breeders care about in the Green Mountain region because of its adaptation to living in all regions, whether mountainous or desert, in addition to the rapid turnover of capital in it, not to mention the consumer’s preference for its distinctive-tasting meat, which is one of the wealth of the national economy and an essential and important source,to supply the population with meat, protein, milk and their derivatives, wool and their by-products that are used as organic fertilizers. The sheep in the Jabal Al Akhdar region are found in the form of flocks whose numbers do not exceed hundreds, and they are raised in traditional methodsThe study dealt with methods of raising and fattening sheep with the open and closed systems, and a comparison between them in breeding in terms of determining the optimal period for breeding and the optimal size of the herd.Most the breeders are raising sheep with Open system, and numbers of the breeders using closed system are (22 breeders) only, and that the most important variables that affect production in both systems (open and closed) are the number of deaths, the amount of feed, the costs of veterinary care, the number of workers and the amount of water, and that the most important problems facing sheep breeders in the study area are problems with feed, and Veterinary, problems in marketing.